Hybrid energy storage system optimal sizing for urban electrical bus regarding battery thermal behavior - Si Mohamed Faresse; Mohamed Assini; Abdallah Saad (Institute of Advanced Engineering and Science, 2020)
This paper proposes an algorithm for sizing the hybrid energy storage system of an urban electrical bus regarding battery thermal behavior. The aim of this study is to get the supercapacitors optimal contribution part in the hybrid energy storage system to keep the battery temperature within its allowable limit. A semi-active parallel topology that uses supercapacitors as a main source of energy is considered. According to the bus mechanical parameters and the ARTEMIS driving cycle, the power and energy demand are calculated. Using mathematical models for the battery, supercapacitors and DC-DC converter, several simulations are performed for different hybridization percentages. While observing the evolution of battery temperature, the most favorable hybridization percentage is defined.